2002
DOI: 10.1046/j.1420-9101.2002.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of syncarpy in angiosperms: theoretical and phylogenetic analyses of the effects of carpel fusion on offspring quantity and quality

Abstract: The repeated evolution of fused carpels (syncarpy) is one of the dominant features of angiosperm macroevolution. We present results of new phylogenetic and theoretical analyses to assess the frequency and nature of transitions to syncarpy, and the possible advantages of syncarpy over apocarpy under a variety of ecological conditions. Using a recent molecular estimate of angiosperm phylogeny, we ascertained that a minimum of 17 independent evolutionary transitions from apocarpy to syncarpy have occurred; about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 37 publications
1
84
0
Order By: Relevance
“…Syncarpy intensifies pollen competition and, thus, may increase the chances of obtaining pollen from the best male parent. In support of this idea, and consistent with an adaptive function, a recent phylogenetic analysis estimates that syncarpy has evolved independently 17-26 times in the flowering plants (Armbruster et al 2002).…”
Section: Inclusion Criteriamentioning
confidence: 62%
“…Syncarpy intensifies pollen competition and, thus, may increase the chances of obtaining pollen from the best male parent. In support of this idea, and consistent with an adaptive function, a recent phylogenetic analysis estimates that syncarpy has evolved independently 17-26 times in the flowering plants (Armbruster et al 2002).…”
Section: Inclusion Criteriamentioning
confidence: 62%
“…Error bars represent 95% confidence interval. compitum in angiosperms with syncarpy (Carr and Carr, 1961;Endress, 1982;Armbruster et al, 2002). Enhanced seed set via pollen tube growth in the extragynoecial compitum occurs because of the ability of pollen tubes from a pollinated carpel to enter the ovary of an unpollinated carpel (Williams et al, 1993;Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The freely flowing exudates between the adjacent carpels have been posited to transmit pollen tubes from one carpel to another, thereby operating as a cryptic extragynoecial compitum (Endress and Igersheim, 2000). In syncarpous angiosperms, a compitum is a region of shared pollen tube transmitting tissue allowing pollen tubes full access to all ovules within a compound ovary (Carr and Carr, 1961;Armbruster et al, 2002). Although structural studies have provided insight into the distribution of gynoecial exudates, data confirming the spatial relationships of pollen tube transmission within and between carpels with respect to the ECM distribution are absent for the Schisandraceae as are data confirming the histo-and immunochemical nature of the ECM.…”
mentioning
confidence: 99%
“…Carr & Carr (1961) considered the compitum (eu-syncarpous ginoecium) as a connection between the carpels that allows pollen tubes from grains germinating on any stigma or part of the stigma to fertilize ovules belonging to more than one carpel. Armbruster et al (2002) found eu-syncarpous gynoecia for all species of Myrtaceae they analyzed, however, there is variation in the degree of development of the compitum.…”
Section: Discussionmentioning
confidence: 85%